2005
DOI: 10.1097/00000542-200505000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Blocks Cholinergic Synaptic Transmission Postsynaptically but Does Not Affect Short-term Potentiation

Abstract: This study demonstrates that sevoflurane blocks cholinergic synaptic transmission postsynaptically but does not affect short-term synaptic plasticity at the visceral dorsal 4-left pedal dorsal 1 synapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…6A-C). These sites of clustering represent the putative synaptic sites at soma-to-soma synapses (Fiumara et al, 2005;Naruo et al, 2005). A more punctate distribution was observed for the non-phosphorylatable mutant Syn Ala36,Ala42 -GFP ( Fig.…”
Section: Phosphorylation Of Helix Synapsin B-domain Modulates Synapsimentioning
confidence: 79%
“…6A-C). These sites of clustering represent the putative synaptic sites at soma-to-soma synapses (Fiumara et al, 2005;Naruo et al, 2005). A more punctate distribution was observed for the non-phosphorylatable mutant Syn Ala36,Ala42 -GFP ( Fig.…”
Section: Phosphorylation Of Helix Synapsin B-domain Modulates Synapsimentioning
confidence: 79%
“…This may be related to sevoflurane dose. Naruo et al [7] reported that cholinergic post-synaptic transmission was inhibited by sevoflurane in a concentration dependent manner. Sato et al [15] found that high Mean ± SD, * = P < 0.05 compared to awake, determined by Tukey tests.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured Lymnaea neurons retain their normal action potential types (Yar and Winlow, 1991; Winlow et al, 1991), transmitter identity (Syed et al, 1990; Spencer et al, 1995; Naruo et al, 2005), responsiveness to applied transmitters (Haydon, 1989; Syed et al, 1990) and responsiveness to applied general anesthetics (Spencer et al, 1995, 1996). Substantial research on the effect of anesthetics on neurotransmission in Lymnaea was accrued in Syed’s laboratory in Calgary.…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%
“…In this case presynaptic transmitter release was unaffected, but postsynaptic nicotinic receptors were blocked in a dose dependent manner. However post-tetanic potentiation (PTP), a form of working memory, established in the absence of the anesthetic was not eliminated by it (Naruo et al, 2005). …”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%